UPAYA INTERNALISASI KITAB TAKLIM MUTAALLIM DALAM MENANAMKAN PENDIDIKAN KARAKTER SANTRI ASRAMA AL MA’MUROH PONDOK PESANTREN DARUSSALAM BLOKAGUNG - Kholiq, Ilham Nur; Jamroh, Nur Maya Badriyatul (International Conference on Humanity Education and Society (ICHES), 2024)
The book Taklimul Mutaallim is one of the phenomenal books written by Sheikh Azzarnuji. This book not only deals with moral education with the aim of forming the character of students, but also discusses how a student can take careful action in order to have moral character towards Allah, teachers and friends. This research aims to investigate in depth the internalization efforts carried out by the Alma'muroh dormitory through studying the book Taklimul Mutaallim. This research used qualitative descriptive approach. Data collection techniques were carried out using interviews, observation and documentation. The results shows that the success of a knowledge seeker is influenced by intelligence, sincerity, patience, sufficient supplies, teacher guidance, and a long time. Meanwhile, the attempt to internalize the values in the book Taklimul Mutaallim in the Al Makmuroh dormitory are carried out by means of mujahadah, reciting rotibulhaddad, book study, social activities of the santri husada, mutual cooperation, sorogan, all of which must be participated in by the female students so that the goal of internalization can be achieved optimally.